LASER BEAM REJECTION INVESTIGATION PASSING THROUGH AIR WITH TEMPERATURE GRADIENT USING THE MONITORING AUTOMATED SYSTEM - Grigoryan, A. M.; Markarian, A. H.; Nersisyan, S. C.; Chilingaryan, U. S.; Elbakyan, V. L. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
In this work was describe the automated experimental assembly, which simulate the optical system of muon registration detectors for small deformations in CERN spectrometer experiment with calculation of laser beam passing through a thermal gradient in air. Comparison of experimental results with theory is carried out.